Creation and Analysis of Artworks (Paintings) in the series “Culture of Happiness”: Suratthani Chak Phra Festival - Sripin, Dechvinit (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2025)
This research article aims to 1) study the tradition of "Chak Phra" in Surat Thani Province, 2) create a series of paintings titled "Culture of Happiness" based on the Chak Phra tradition of Surat Thani the research constitutes a creative inquiry within the field of artistic creation, and 3) disseminate the "Culture of Happiness" painting series to the public. The creative research process involves 1) studying and understanding the Chak Phra tradition of Surat Thani Province, 2) Using the prototype image data that reflects impression, color, and beauty, incorporating Paul Gauguin's idea that "color" is like musical sound that resonates. It is the most ordinary thing, but it results in something difficult to describe with words, which is its inner force to create a painting, and 3) exhibiting the "Culture of Happiness" painting series to the public. The research findings indicate that 1) The Chak Phra tradition is a local custom of the southern Thai people that has been practiced since the Srivijaya period. It is a Buddhist tradition observed one day after the end of the Buddhist Lent, on the first waning moon of the 11th lunar month. Buddhists gather to place Buddha images on a ceremonial vehicle such as a boat, car, or float known as "Phanom Phra Boat" and parade it through the streets. This practice is believed to bring blessings and happiness according to ancient beliefs. 2) The creative process resulted in seven oil paintings on canvas, each measuring 60x80 cm: 1) "Happiness of the Dancer at the Boat's Bow", 2) "Joy of Unity", 3) "Happiness of the Long Drum", 4) "Happiness Beyond Sight", 5) "Rhythm of Happiness", 6) "Smiles of the Blue Dancer", and 7) "Night of the Eleventh Moon" along with the conceptual ideas behind them. 3) The dissemination of the "Culture of Happiness: Surat Thani Chak Phra Tradition" painting series to the public at the Srivijaya Art Gallery, Faculty of Humanities and Social Sciences, Surat Thani Rajabhat University, has increased awareness and appreciation of the long-standing cultural heritage.